Analysis of the selection of materials for road construction taking into account the carbon footprint and construction costs - Damian Wieczorek; Krzysztof Zima (Archives of Civil Engineering, 2022)
The analysis of the costs and emissions of greenhouse gases for individual phases of construction investments allows for the implementation of solutions and the prevention of negative environmental impacts without significantly increasing construction costs. The share of individual investment phases in the amount of carbon dioxide (CO2) produced for the construction and use of buildings depends mainly on the materials used and the implemented design solutions. In accordance with the idea of sustainable construction, materials and design solutions with the lowest possible carbon footprint should be used. This can be achieved by using natural building materials, materials subjected to appropriate chemical composition modifications, or materials in which their production does not require large amounts of energy. The aim of the article is to determine the value of the purchase costs of selected road materials (concrete paving blocks, cement-sand bedding, concrete curbs, semi-dry concrete and concrete underlay, washed sand, and crushed aggregate with a fraction of 0–31.5 mm) for the implementation of a road investment. In addition, the authors focused on determining the size of the embodied carbon footprint due to GHG (greenhouse gas) emissions and GHG removals in a product system, expressed as CO2 equivalents for the same materials that were subjected to cost analyzes. The article presents the results of original analyzes, and indicates the optimal solutions in terms of minimizing the cost of purchasing road materials and minimizing the carbon footprint. The discussion also covers the issue of changing the chemical composition in the context of the potential impact on the reduction of material costs and CO2 equivalent emissions.